Pythagorean Theorem:
a^2 + b^2 = c^2
Since you have the hypotenuse, you can change the equation to find the missing side.
a^2 - c^2 = - b^2
Insert your numbers:
9^2 - 10^2 = -b^2
What do you get?
Answer:
sorry you can send me picture of work
Step-by-step explanation:
ok send me and get answers
We are given with the equation <span>f(x) = ax3 + bx2 + cx + d
Substituting, (3,11)
</span><span>11= 27a + 9b + 3c + d
</span><span>@(5, 9)
</span><span>9 = 125 a + 25 b + 5c + d
@</span><span>(4, 10)
</span><span>10 = 64 a + 16 b + 4c + d
@inflection point, second derivative is equal to zero
</span><span>f'(x) = 3ax2 + 2bx + c
</span>f''(x) = 6ax + 2b = 0
when x is 4, 24 a + 2b = 0 or 12a + b = 0.
There are 4 equations, 4 unknowns: answer is
<span>0.5 x^3 - 6x^2 + 22.5 - 24 = 0</span>
Answer:
Option A and B are correct
Step-by-step explanation:
We have to add here
6x+5y=1.
6x-5y=7
sow e will get 12x=8 , x=8/12=2/3
Option A is correct.
If We substract bottom from furst then
6x+5y=1
-6x+5y=-7
10y=-6
y=-6/10=-3/5
we put y=-3/5 in any equation and find x
6x+5(-3/5)=1
6x=4
x=4/6=2/3
So Option B also correct.
The answer is to 27/45 is 3/5